Factors associated with quality of life among caregivers of special needs children in Terengganu, Malaysia - Karimah Fakhriah, Ismail; Aryati, Ahmad; Sakinah, Harith; Lin, L.P; Wan Pauzi, Wan Ibrahim; Wan Rohani, Wan Taib; Sherryneis Ezra, . (2019)
Background: Living with special needs children requires a life-long adjustment. Parents have to adapt to the condition that consequently may possess a large impact on their overall health and well-being. This paper evaluates the sociodemographic factors and physical characteristics associated with the quality of life (QoL) among caregivers of special needs children in community-based rehabilitation centre Terengganu. Methods: A total of 183 caregivers involved in this cross-sectional study. This study was conducted in all 46 rehabilitation centres across Terengganu state. Validated Malay Version World Health Organization Quality of Life-BREF (WHOQOL-BREF) Questionnaire was used to assess the QoL of these caregivers based on physical health, psychological health, social relationship and environment domain. Results: The lowest QoL score obtained was in the physical health domain (64.30 [17.90]) followed by environmental support domain (65.60 [18.70]), psychological wellbeing (70.80 [20.90]) and social relationship domain (75.00 [16.60]). There was a significant difference between family income with all QoL domains by which the tertiary education caregivers score significantly higher in the environmental support domain. Meanwhile, child’s texture acceptance was significantly different between two groups for the physical health (Pvalue=0.030) and psychological wellbeing (P-value=0.022). Family income, child’s texture acceptance and seizure episodes were predictors for variations in QoL domain score obtained by the caregivers. Conclusion: This study found that parents with all types of child’s disability scored the lowest for environment domain in QoL. Parents with special need children were currently living with affected QoL. Therefore, more support and intervention should be offered to the parents to enhance overall well-being that consequently will improve the child’s QoL.